2017
DOI: 10.1053/j.gastro.2016.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Heterotrimeric G Stimulatory Protein α Subunit Is Required for Intestinal Smooth Muscle Contraction in Mice

Abstract: Gsa is required for intestinal smooth muscle contraction in mice, and its levels are reduced in ileum biopsies of patients with chronic intestinal pseudo-obstruction. Mice with disruption of Gnas might be used to study human chronic intestinal pseudo-obstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…Moreover, consideration about the synthetic phenotype of Gsα-deficient smooth muscle cells, Gsα deletion might increase the angiogenesis and reduce the vascular resistance in the small vessels. In our previous study, Gsα deficiency impaired intestinal smooth muscle contraction [20], which affect their food intake. Thus, Gsa SMKO mice exhibited the phenotype of lower body weight.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Moreover, consideration about the synthetic phenotype of Gsα-deficient smooth muscle cells, Gsα deletion might increase the angiogenesis and reduce the vascular resistance in the small vessels. In our previous study, Gsα deficiency impaired intestinal smooth muscle contraction [20], which affect their food intake. Thus, Gsa SMKO mice exhibited the phenotype of lower body weight.…”
Section: Discussionmentioning
confidence: 88%
“…However, mice overexpressing a dominant negative Gsα-mutant in heart leads to decreased β-adrenergic responsiveness and is protective against ISO-induced hypertrophy [19]. In our recent report, we found that Gsα could regulate intestinal smooth muscle contraction in mice [20]. However, the roles of Gsα in the SMC phenotype switch and AAA formation are undefined.…”
Section: Introductionmentioning
confidence: 99%
“…The contraction in the smooth muscle of the intestine in response to various agents is often composed of two phases: phasic, fast, and unsustainable component followed by a tonic, slow, and sustained component. The mechanism responsible for the phasic component is related to the activation of a metabotropic receptor coupled to protein G. On the other hand, the tonic component is mainly mediated by calcium influx through voltage-dependent calcium channels (Ca V ) (Bolton, 1979;van Breemen & Saida, 1989;Murthy, 2006;Sakamoto et al, 2007;Qin et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Until now, most of the research has been devoted to understanding adenosinesignaling in the myenteric plexus; however, data concerning the physiological relevance of AMP and related ecto-enzymes CD73 and ADA in controlling adenosine levels in gut IMFs are still limited [8-10, 15, 19]. Smooth muscle myopathies have been observed in various gastrointestinal diseases, including chronic intestinal pseudo-obstruction (CIP) [26] and inflammatory bowel disease (IBD) [27][28][29]. IMFs show morphologic and functional features of both fibroblasts and smooth muscle cells and appear to transdifferentiate from these cells or to originate from primitive stem cells.…”
Section: Discussionmentioning
confidence: 99%